2010
DOI: 10.1039/c0cc01562h
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient and noble metal-free NiS/CdS photocatalysts for H2 evolution from lactic acid sacrificial solution under visible light

Abstract: We report the synthesis of highly active NiS/CdS photocatalysts via a simple hydrothermal loading method for H(2) evolution from lactic acid sacrificial solution under visible light. In the absence of noble metals, a high quantum efficiency of 51.3% was measured at 420 nm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
276
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(295 citation statements)
references
References 29 publications
16
276
0
Order By: Relevance
“…It is noteworthy that the highest QE reported so far for photocatalytic hydrogen production without noble metal loading is 51% (ref. 16). While our photocatalyst reaches 62%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the highest QE reported so far for photocatalytic hydrogen production without noble metal loading is 51% (ref. 16). While our photocatalyst reaches 62%.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, at the most basic level, enhancing charge separation and preventing their recombination before they move to the surface-reactive sites of the photocatalyst have key roles in determining the solar energy conversion efficiency. To this end, many strategies have been investigated, including in situ photodeposition of noble metal as cocatalysts onto photocatalyst surface, chemical doping to form donor or acceptor energy levels within the band gap of the photocatalyst, and development of Z-scheme systems [16][17][18][19][20] . Among these approaches, coupling of two different materials or phases at the nanoscale to form heterojunctions has proven successful, owing to improved interfacial charge transfer and therefore effective charge separation [20][21][22][23] .…”
mentioning
confidence: 99%
“…[11,[20][21][22][23] In recent years, co-catalysts composed of earth-abundant elements have been explored aggressively to replace Pt as the extreme scarcity and high price of Pt restricts the massive application of photocatalysts such as Zn x Cd 1Àx S for large-scale solar H 2 production. [24] Especially, materials based on Ni, such as Ni, [25,26] NiS, [27,28] NiO, [26,[29][30][31] and Ni(OH) 2 , [5,32,33] are among the most active co-catalysts loaded on various semiconductor photocatalysts to achieve highly efficient and cost-effective photocatalytic H 2 production. For example, Dinh et al reported that the presence of Ni clusters as a co-catalyst could enhance the photocatalytic H 2 -production rate of a CdS-titanate nanocomposite by more than 77 times.…”
Section: Introductionmentioning
confidence: 99%
“…[14] In addition, nickel sulfides can form various phases, [15] such as NiS, Ni 3 + x S 2 , Ni 3 S 2 , Ni 7 S 6 , Ni 3 S 4 , and NiS 2 , and have multiple applications, including as photocatalysts for H 2 evolution, [16] possible transformation toughener, [17] cathode materials for rechargeable lithium batteries, [18] or as a highboiling solvent for all-solid-state lithium secondary batteries. [19] Furthermore, Du's group introduced the application of iron/ nickel sulfide filled carbon nanotubes and their microwave-absorbing properties, [20] with a maximum reflection loss of À29.58 dB.…”
Section: Introductionmentioning
confidence: 99%